Formulation and evaluation of Norfloxacin gastro retentive drug delivery systems using natural polymers - Thahera, P D; Ashok, Mr; Latha, K; Shailaja, T; Nyamathulla, S; Uhumwangho, M U (International Current Pharmaceutical Journal, 2012)
Gastric retentive floating drug delivery system (GFDDS) is enabled the prolonged continuous input of the drug to the upper parts of the gastrointestinal (GI) tract and improves the bioavailability of medications with narrow absorption window. The design of the delivery system is based on the controlled release formulation with floating and swelling features in order to prolong the gastric retention time of the drug delivery systems. In the present study norfloxacin as candidate, guar gum, sodium CMC, HPMC15 KM is studied along with other excipients like PVP K30 (binder), sodium bicarbonate microcrystalline cellulose were used in different concentrations to get the desired controlled release profile over a period of 12 hrs. All the formulations were evaluated for buoyancy lag time, duration of buoyancy, dimensional stability, drug content and in vitro drug release profile. Based on the in vitro studies carried out for the optimized formulation by dissolution the performance of the developed formulation promises to be efficient in controlling the drug release rate with the guar gum, a natural polymer. DOI: http://dx.doi.org/10.3329/icpj.v1i7.10809 International Current Pharmaceutical Journal 2012, 1(7): 155-164